Reproducibility of a novel, vacuum‐assisted immobilization for breast stereotactic radiotherapy. Issue 3 (3rd March 2021) - Snider, James W.; Nichols, Elizabeth M.; Mutaf, Yildirim D.; Chen, Shifeng; Molitoris, Jason; Diwanji, Tejan; Becker, Stewart J.; Feigenberg, Steven J.
Abstract: A novel, breast‐specific stereotactic radiotherapy device has been developed for delivery of highly conformal, accelerated partial breast irradiation. This device employs a unique, vacuum‐assisted, breast cup immobilization system that applies a gentle, negative pressure to the target breast with the patient in the prone position. A device‐specific patient loader is utilized for simulation scanning and device docking. Prior to clinical activation, a prospective protocol enrolled 25 patients who had been or were to be treated with breast conservation surgery and adjuvant radiotherapy for localized breast cancer. The patients underwent breast cup placement and two separate CT simulation scans. Surgical clips within the breast were mapped and positions measured against the device's integrated stereotactic fiducial/coordinate system to confirm reproducible and durable immobilization during the simulation, treatment planning, and delivery process for the device. Of the enrolled 25 patients, 16 were deemed eligible for analysis. Seventy‐three clips (median, 4; mean, 4.6; range, 1–8 per patient) were mapped in these selected patients on both the first and second CT scans. X, Y, and Z coordinates were determined for the center point of each clip. Length of vector change in position was determined for each clip between the two scans. The mean displacement of implanted clips was 1.90 mm (median, 1.47 mm; range, 0.44–6.52 mm) (95% CI, 1.6–2.20 mm). Additional analyses stratified clips by position within the breast and depth into the immobilization cup. Overall, this effort validated the clinically utilized 3‐mm planning target volume margin for accurate, reliable, and precise employment of the device.